2019 IEEE 30th Annual International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC) 2019
DOI: 10.1109/pimrc.2019.8904212
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Super-Nyquist CAP Modulation based VLC with Low Bandwidth Polymer LEDs

Abstract: Visible light communication systems often suffer from high frequency attenuation when transmitting outof-band. This effect has been ameliorated by multi-band modulations such as multi-band carrier-less amplitude and phase (m-CAP), which minimises the effect of decreased high frequency magnitude and maximises signal-to-noise ratio-per-sub-band. On the other hand, in the pass-band region, super-Nyquist CAP (SCAP) can offer throughput improvements with no additional complexity at the receiver, at the cost of bit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In this variant, typically referred to as super-Nyquist (SN-CAP), the spacing between the CAP subbands is reduced in order to increase the spectral efficiency of the scheme [96,[124][125][126]. However, this results in spectral overlap (band interference) between adjacent bands which destroys the orthogonality of the respective pulse shaping filters and in the distortion of the transmitted waveforms.…”
Section: (I) Modified Pulse Shapesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this variant, typically referred to as super-Nyquist (SN-CAP), the spacing between the CAP subbands is reduced in order to increase the spectral efficiency of the scheme [96,[124][125][126]. However, this results in spectral overlap (band interference) between adjacent bands which destroys the orthogonality of the respective pulse shaping filters and in the distortion of the transmitted waveforms.…”
Section: (I) Modified Pulse Shapesmentioning
confidence: 99%
“…Additionally in [96], it has been demonstrated that the induced IBI can be modelled as a MIMO system and therefore appropriate equalizers can be deployed to mitigate IBI and enable the successful symbol recovery on each subband. Hybrid super-Nyquist multi-band CAP schemes have also been proposed where some of the subbands are overlapped and some are kept orthogonal as in conventional m-CAP [126], achieving a balance between induced IBI and channel crosstalk (non-orthogonality) due to the non-flat frequency response of the channel. The scheme has been shown to achieve better performance than the respective conventional m-CAP and pure SN-CAP in an OLED-based VLC link [126].…”
Section: (I) Modified Pulse Shapesmentioning
confidence: 99%
See 1 more Smart Citation